Fertility outcome after intracytoplasmic sperm injection with surgically retrieved sperm in obstructive and non-obstructive azoospermia - Hooda, Ruchi; Gopinathan, K. K.; Devi, Geeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Azoospermia is a highly upcoming subject in the last few decades. In the past, use of donor sperm was the only option providing a realistic chance of conception for couples affected by azoospermia. Introduction of sperm retrieval techniques and assisted reproductive technologies, especially intracytoplasmic sperm injection (ICSI), has provided these men a chance to father their genetically own child and changed the management approach significantly. The aim of this study was to compare the outcome of intracytoplasmic sperm injection (ICSI) of surgically retrieve sperms between couples with infertility due to male non-obstructive azoospermia (NOA) and obstructive azoospermia (OA). Methods: It was a retrospective observational study and data analysis was conducted at Centre for Infertility and Assisted Reproduction (CIMAR), Edappal, Kerala, India from January 2018 to December 2021. The selection of cases was based on detailed history, physical examination, husband’s semen analysis confirmed twice and hormone profile. During a period of four years, 754 azoospermic patients were diagnosed at our centre. In this study, female age <35 years considered as the inclusion criteria as female age plays a pivotal role for IVF/ICSI outcome, while patient in whom voluntary donor sperm used, patients in whom sperm retrieval failed, female age >35 years and female associated with any pathology which can alter the treatment outcome e.g., endometriosis, severe adenomyosis, diminished ovarian reserve, fibroid uterus were excluded from the study groups. On the basis of serum FSH, serum testosterone and testicular size and considering inclusion and exclusion criteria, patients were subdivided into two group as: group A (n=75) included patients with non-obstructive azoospermia and group B (n=75) included patients with obstructive azoospermia, underwent ICSI. Results: Clinical pregnancy rate, fertilization and implantation rate were found to be higher in OA cases in comparison to those of NOA cases. Grade A embryo formation rate and miscarriage rate showed no significant difference. Conclusions: As the cause of azoospermia is different in both the groups, the chances of achieving a successful outcome (fertilization rate, embryo formation rate, and clinical pregnancy rate) after ICSI are negatively affected by the type of azoospermia and are reduced in men with NOA in comparison to patients with OA.